Disposal of the damaged endowment in Islamic jurisprudence (NTU journal for Administrative and Human Sciences (JAHS), 2022)
In this note, I dealt with the issue of disposing of damaged endowments, in order to answer the problem of the basic study that revolves around the disposal of damaged endowments in Islamic jurisprudence, and what are the controls set by the jurists for this behavior? The memorandum contained two main requirements: The first requirement: revolves around the definition of the endowment and the evidence for its legitimacy and importance. The second requirement: it revolves around the disposal of the damaged endowment, its provisions and controls. The memorandum concluded by mentioning the most important results reached through the study, and some important recommendations.